Development Of Laminated Rubber-Metal Spring Using Standard Malaysia Rubber Constant Viscosity-60 - Salim , Mohd Azli; Putra, Azma; Abdullah, Mohd Azman; Ahmad, Nazirah (Praise Worthy Prize, 2014)
Laminated rubber-metal spring is a new challenging research because previously,it is known as s rubber bearing and its application confined to the field of civil engineering.With the creation of this research,they may applied to mechanical engineering because it was believed could reduce the level of vibration in the car engine system.This paper presents the development of laminated rubber-metal spring which is the key ingredient is standard Malaysia rubber constant viscosity - 60.There are several steps involved to develop the product by different number of degree of freedom and it is discussed in details.Many standard are adopted from open literature and it need to be followed every single step to make this product more reliable and trustworthy data for presentation and future analysis.Overall,the discussion of developing this product is come out together with several figure to present it well.